2017
DOI: 10.1002/app.45879
|View full text |Cite
|
Sign up to set email alerts
|

Role of surface chemistry and morphology in the reactive adsorption of metal ions on acid modified dry bean pods (Phaseolus vulgaris L.) organic polymers

Abstract: The present study aimed at verifying the acid surface modification of dry bean pods subjected to alkaline pretreatment using tannic acid, poly(acrylic acid), and poly(acrylamide‐co‐acrylic acid) and evaluate their performances as adsorbents in the metal ions removal. Factorial design was used as a tool to study the variables that affects the modification processes. The results showed that there was an increase in the adsorption capacity after acidic changes, mainly for the tannic acid, achieving 45% increasing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 32 publications
0
4
0
2
Order By: Relevance
“…Dessa maneira, faz-se necessário que esses resíduos vegetais antes de serem utilizados como adsorventes ou coagulantes passem por pré-tratamento. Além disso, o pré-tratamento melhora as condições de coagulação do resíduo por conta do aumento da porosidade e da área superficial (RAULINO et al 2018). Raulino et al (2018) relatam que a utilização de solução alcalina altera tanto a estrutura fina e morfologia da fibra, como também a conformação de cadeias de celulose, produzindo mudanças na resistência, no brilho da fibra e na capacidade de coagulação.…”
Section: Desenvolvimento (Resultados E Discussões)unclassified
“…Dessa maneira, faz-se necessário que esses resíduos vegetais antes de serem utilizados como adsorventes ou coagulantes passem por pré-tratamento. Além disso, o pré-tratamento melhora as condições de coagulação do resíduo por conta do aumento da porosidade e da área superficial (RAULINO et al 2018). Raulino et al (2018) relatam que a utilização de solução alcalina altera tanto a estrutura fina e morfologia da fibra, como também a conformação de cadeias de celulose, produzindo mudanças na resistência, no brilho da fibra e na capacidade de coagulação.…”
Section: Desenvolvimento (Resultados E Discussões)unclassified
“…The solution pH may affect the degree of ionization, functional group dissociation, adsorbate structure, and adsorbent surface functionality . The pH pcz determination of an adsorbent allows us to identify trends in the variations of surface charge as a function of pH. , pH pcz around 7.0 was found for FA-AT7 (Figure a), indicating the presence of a positive surface charge in solutions whose pH is below this value and a negative surface charge at a higher pH . Nairi et al studied pH pcz for mesoporous silicas MCM-41 and SBA-15 types and found pH pcz to be around 6.0.…”
Section: Resultsmentioning
confidence: 99%
“…The factorial design methodology, unlike experiments that vary one factor at a time, is an excellent tool for the individual study, as well as for the interaction effects of all parameters simultaneously, since the variables can influence each other and the ideal value for one of these variables may depend on the values of other variables. This interaction between variables is a recurrent phenomenon …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations